Effects of forearm wearable resistance during accelerated sprints: From a standing start position. Issue 22 (17th November 2021) - Uthoff, Aaron M.; Macadam, Paul; Zois, James; Nagahara, Ryu; Neville, Jono; Cronin, John B.
ABSTRACT: Fusiform weighted garments enable specific loading strategies during sport-specific movements. Loading the arms over during accelerated sprinting from a 2-point start position is pertinent to a variety of sporting performances. Fourteen sprint-trained individuals (age = 20.61 ± 1.16 years; height = 1.73 m ± 3.85 cm; body mass 65.33 ± 4.86 kg; personal best 100-m race time 11.40 ± 0.39 s) performed unloaded/loaded wearable resistance (WR) sprints. Between-condition step kinematics and kinetics were compared over four acceleration phases: steps 1–4, 5–8, 9–12 and 13–16. Sprint performance did not differ between unloaded and loaded WR at 10-m (−1.41%; ES = −0.32), or 30-m (−0.76%; ES = −0.24). Sprinting with forearm WR significantly decreased step frequency during phase two (p < 0.05, −3.42%; ES = −0.81) and three (−3.60%; ES = −0.86) and step velocity during phase four of the 30 m sprinting task (p < 0.05, −3.61%; ES: 0.91) only. There were no significant differences (p ≤ 0.05) between step kinetics amongst the two conditions. Findings indicate that arm-loaded WR may provide specific sprinting overload for 2-point starting positions. This may be relevant to a wider sporting context such as field and team sport performances.